Shareholder Litigation and Ownership Structure: Evidence from a Natural Experiment - Crane, Alan D.; Koch, Andrew (Management Science, 2018)
We use a natural experiment to identify a causal effect of the threat of shareholder litigation on ownership structure, governance, and firm performance. We find that when it becomes harder for small shareholders to litigate, ownership becomes more concentrated and shifts from individuals to institutions. Director and officer governance protections drop among these firms, and operating performance drops among firms whose ownership structure does not change. These results suggest that the ability of shareholders to coordinate and litigate against management is important for governance. This paper was accepted by Lauren Cohen, finance.